PROTOTYPE UI / UX APLIKASI RESERVASI DI SANGU AKEUL CIGALEUH MAJALENGKA MENGGUNAKAN METODE GDD - Nurazizah, Riri; Suhendri; Nida, Milhatun (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The rapid growth of the culinary industry encourages the integration of technology to improve service quality and operational efficiency. This study aims to design a reservation application prototype for Sangu Akeul Cigaleuh Majalengka, a traditional restaurant that emphasizes cultural values and authentic flavors. The research applied the Goal-Directed Design (GDD) method, consisting of six stages: research, modeling, requirement, framework, refinement, and support. Data were collected through observation and interviews, then developed into user personas, user flows, and a Hierarchical Task Analysis (HTA). The initial design was visualized through wireframes and later refined into an interactive prototype. Usability evaluation was conducted using the System Usability Scale (SUS) with five respondents. The test results indicated an average SUS score of 81.0, categorized as Grade B (Good). These findings demonstrate that the GDD method is effective in producing a functional, user-friendly reservation application that aligns with user needs in the context of traditional culinary businesses.